Emergence of hybrid escherichia coli strains - Gomes, Tânia Aparecida Tardelli; de Mello Santos, Ana Carolina; Hernandes, Rodrigo Tavanelli [UNESP]; Arias-Guerrero, Monica Yurley; Farfán-García, Ana Elvira; Gómez-Duarte, Oscar G. (Springer Nature, 2023)
Hybrid pathogenic Escherichia coli strains combine genetic markers from two distinct pathotypes of diarrheagenic E. coli (DEC) or comprise strains that combine markers from extraintestinal pathogenic E. coli (ExPEC) and DEC simultaneously. The hybrid definition may include strains isolated at extraintestinal sites with one or more DEC-defining virulence factor (VF)-encoding genes. We provide an overview of the studies reporting the different combinations of VF that result in hybrid strains, some of which are associated with more severe clinical complications. Genomic analysis of some hybrid strains supports the hypothesis that the emergence of hybrid strains results from horizontal gene transfer (HGT) among E. coli strains, either among DECs or among DEC and ExPEC strains. The continuous search for hybrid pathogenic E. coliepidemiology, geographic location, risk factors for infection, transmissibility, zoonosis, and prevention. Additional research is required to understand their origin, evolution, genetic plasticity, and pathogenesis. Public health authorities face a significant challenge to promptly identify and prevent these pathogens from spreading and causing outbreaks.